Contribuições da fenomenologia para o ensino da geografia - Paiva, Rogério Alves de (2009)
This work is proposed to develop a study of the relationships between man and nature in a Phenomenological Geography approach seeking theoretical and methodological alternatives witch promote new perspectives of teaching for the student. To do so, a survey of the life of primitive peoples was done in order to get more intimate relations with the Nature, as well as, aspects of contemporary man s contact with the natural world. Based on the conceptions of geographicity in Eric Dardel, the study of the Earth was analyzed in a perspective that exceeds the spacephysics elements of the objective science, the geometric and measurable space. We sought to understand the world as a consequence of an intersubjective phenomenon, in which the relations of the human body with the Earth assume a decisive character for the understanding of a teaching-learning process turned to the space experienced in life. From the notions of spatiality, we tried to discuss the construction of the space in a phenomenological vision. For the inquiry, the qualitative methodology was used due to its documentary and bibliographical character. The essential assumptions in the teaching of Geography present themselves still filled up with a distant reality of the immediate spatial relations of student. In this way, the present research aims to contribute both to strengthen the discussions that are locked around theoretical and methodological issues in this area of education, but also to the Geography in school be associated with an education conception that aims at the formation of individuals able to relate to the Nature in a physical perspective, waking up so, other ways to see the Earth highlighting the original dimension of human existence.